How green was our classroom - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
If ever proof was needed that the impact of an on-the-spot study visit can be worth several times that of an abstract distance-learning seminar, here it is.